Influence of surface activation on the microporosity of PE‐CVD and PE‐ALD SiOx thin films on PDMS. Issue 4 (22nd January 2022) - Hoppe, Christian; Mitschker, Felix; Mai, Lukas; Liedke, Maciej Oskar; de los Arcos, Teresa; Awakowicz, Peter; Devi, Anjana; Attallah, Ahmed Gamal; Butterling, Maik; Wagner, Andreas; Grundmeier, Guido
Abstract: The microporosity, structure and permeability of SiO x thin films deposited by microwave plasma‐enhanced chemical vapour deposition (PE‐CVD) and plasma‐enhanced atomic layer deposition (PE‐ALD) on polydimethylsiloxane (PDMS) substrates were investigated by positron annihilation spectroscopy and complementary technique, such as X‐ray photoelectron spectroscopy, infrared spectroscopy, time of flight mass spectroscopy and atomic force microscopy. The SiO x films were deposited onto spin‐coated PDMS substrates, which were previously exposed to an oxygen plasma thus achieving the conversion of the top polymer layer into SiO x . The presence of this oxidised surface near the region led to an overall decrease in micropore density and to a shift towards smaller pore sizes within the deposited SiOx films. A correlation between the oxygen fluence during the oxygen plasma treatment and the microporosity of the PE‐CVD and PE‐ALD SiO x films could be established. Abstract : The intrinsic porosity of plasma deposited SiO x thin films onto polydimethylsiloxane (PDMS) polymers can be controlled by plasma preconditioning of the PDMS before deposition. Oxidising plasma treatment of the PDMS results in the conversion of the top PDMS into a SiO x ‐like surface onto which additional SiO x is deposited. Different plasma pretreatment conditions result in measurable porosity differences in the SiO x deposited by plasma‐enhanced chemical vapour deposition and plasma‐enhanced atomic layer deposition.